R&D and private investment: How to conserve indigenous fruit biodiversity of Southern Africa - Hermann Waibel; Justus Wesseler; Dagmar Mithöfer (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
Indigenous fruits contribute widely to rural incomes in Southern Africa but their availability is declining. A domestication program aims to increase farm-household income and conserve biodiversity through farmer-led tree planting. Planting domesticated indigenous fruit trees is an uncertain, irreversible but flexible investment. Our analysis applies the real option approach using contingent claims analysis, which allows solving the discounting problem. The article analyses (1) to what level fruit collection cost and/or (2) the necessary technical change, i.e. breeding progress, have to rise in order to render tree planting economical, using data from income portfolios of rural households in Zimbabwe. Results currently show that collecting indigenous fruits is more profitable than planting the trees. A combination of technical change and decrease in resource abundance can provide incentives for farmer-led planting of domesticated trees and biodiversity conservation. However, breeding progress must be significant for investment in tree planting to be economically attractive.
Keywords: Q16; Q23; O13; Q01; 330; indigenous fruits; real option; technology adoption; uncertainty; ex ante impact assessment; Zimbabwe